Essays on the history of economics - Samuels, Warren J., 1933- (Routledge studies in the history of economics, 2004)
Under the impressive editorship of Warren Samuels et al, this book addresses the state of the history of economic thought today. A relevant and important contribution to economics that will develop an unsurprising number of fans.